Collaborative networks and the need for a new management language. Issue 3 (16th March 2017) - Mandell, Myrna; Keast, Robyn; Chamberlain, Dan
ABSTRACT: Language is a key element for the formation of social identity and cohesion and is important for setting the tone for the way that people behave with and to each other. The aim of this paper is to highlight the need for a distinct language that better describes and shapes the thinking and practice of collaborative networks and collaboration generally. We argue that development of a specialized language for collaborative networks is necessary to better reflect their distinctive characteristics and operating logic, including higher levels of cohesion, communication and collective action. Using two collaborative case examples we specifically focus on how this new language engenders changed, more collaborative practice and relates to the unique way management and leadership are practiced in collaborative networks.